Transcriptional switch of the dia1 and impA promoter during the growth/differentiation transition - Hirose, S; Mayanagi, T; Pears, C; al., E (American Society for Microbiology, 2005)
When growth stops due to the depletion of nutrients, Dictyostelium cells rapidly turn off vegetative genes and start to express developmental genes. One of the early developmental genes, dia1, is adjacent to a vegetative gene, impA, on chromosome 4. An intergenic region of 654 bp separates the coding regions of these divergently transcribed genes. Constructs carrying the intergenic region expressed a reporter gene (green fluorescent protein gene) that replaced impA in growing cells and a reporter gene that replaced dia1 (DsRed) during development. Deletion of a 112-bp region proximal to the transcriptional start site of impA resulted in complete lack of expression of both reporter genes during growth or development. At the other end of the intergenic region there are two copies of a motif that is also found in the carA regulatory region. Removing one copy of this repeat reduced impA expression twofold. Removing the second copy had no further consequences. Removing the central portion of the intergenic region resulted in high levels of expression of dia1 in growing cells, indicating that this region contains a sequence involved in repression during the vegetative stage. Gel shift experiments showed that a nuclear protein present in growing cells recognizes the sequence GAAGTTCTAATTGATTGAAG found in this region. This DNA binding activity is lost within the first 4 h of development. Different nuclear proteins were found to recognize the repeated sequence proximal to dia1. One of these became prevalent after 4 h of development. Together these regulatory components at least partially account for this aspect of the growth-to-differentiation transition.